The criminal subject : Alphonse Bertillon and Francis Galton, their aesthetics and their legacies - Francis, Melanie Sarah Jane (2013)
This thesis applies aesthetic language to a variety of practices associated with the production and analysis of criminal identification portraits. Much of what might seem to be standardised in this model of portraiture was influenced by abstract visual techniques that were developed in the late nineteenth century, specifically in the work of Alphonse Bertillon and Francis Galton, which frequently moves away from the judicial, into the experimental. Structured theoretically as opposed to chronologically, this thesis provides a thorough examination of the components - material, technological, temporal, and symbolic - that constitute the identification portrait.